Erroneous diagnosis of small cell lung cancer based on small biopsies with far-reaching consequences: case report of a typical carcinoid tumor - Kyritsis, Ioannis; Krebs, Bettina; Kampe, Sandra; Theegarten, Dirk; Aigner, Clemens; Welter, Stefan (Journal of Thoracic Disease, 2017)
Although neuroendocrine tumors (NETs) of the lung are frequently discussed together, carcinoids are very different from high-grade small cell lung carcinoma (SCLC). SCLC is found in heavy-smoking, older patients, whereas smoking is not strongly associated with carcinoid tumors. We present the case of a 46-year-old never smoking woman who was misdiagnosed with SCLC. The patient was not responsive to radio-chemotherapy plus prophylactic cranial irradiation (PCI); she had a typical carcinoid (TC) tumor according to the final pathology report. We aim to demonstrate that diagnosis of SCLC based on cytology or small biopsy specimens must be scrutinized when the clinical constellation is unusual, or when the follow-up assessment shows no response to systemic treatment.